Meningkatkan Kemampuan Kognitif Anak Membuat Pola ABCD-ABCD Sate Buah - Sriyani Sriyani; Syamsiah Djaga; Andi Mardiana (Universitas Negeri Makassar, 2022)
This study aims to improve the cognitive abilities of early childhood in making ABCD-ABCD patterns through activities of making ABCD-ABCD patterns using fruit satay in group B students at Mandala Putra Kindergarten. The subjects of this study were 5 students of group B of TK Mandala Putra. The object of this research is the cognitive ability of early childhood in making ABCD-ABCD patterns using fruit satay. The data collection technique used was observation of the students' work to determine the level of children's cognitive abilities in making ABCD-ABCD patterns and evaluation was also carried out during children's activities. The data analysis technique in this research is descriptive quantitative. Based on the results of data analysis carried out, it was obtained that learning completeness in the pre-cycle had a percentage of 20%, in the first cycle it had a percentage of 40%, and in the second cycle it had a percentage of 60%. And from the results of the analysis above, it can be interpreted that the activity of making ABCD-ABCD patterns using fruit satay can improve the cognitive abilities of group BPenelitian ini bertujuan untuk meningkatkan kemampuan kognitif anak usia dini dalam membuat pola ABCD-ABCD melalui kegiatan membuat pola ABCD-ABCD dengan menggunakan sate buah pada anak didik kelompok B di TK Mandala Putra. Subjek dari penelitian ini adalah 5 peserta didik kelompok B TK Mandala Putra. Objek dari penelitian ini adalah kemampuan kognitif anak usia dini dalam membuat pola ABCD-ABCD dengan menggunakan sate buah. Teknik pengumpulan data yang digunakan adalah observasi terhadap hasil karya peserta didik untuk mengetahui tingkat kemampuan kognitif anak dalam membuat pola ABCD-ABCD dan dilakukan pula evaluasi selama kegiatan anak dilaksanakan. Teknik analisis data pada penelitian ini adalah deskriptif kuantitatif. Berdasarkan hasil analisis data yang dilakukan diperoleh ketuntasan belajar pada pra-siklus memiliki persentase sebesar 20 %, pada siklus I memiliki persentase sebesar 40 %, dan pada siklus II memiliki persentase sebesar 60 %. Dan dari hasil analisis di atas dapat diartikan bahwa kegiatan membuat pola ABCD-ABCD dengan menggunakan sate buah dapat meningkatkan kemampuan kognitif anak didik kelompok B